A biography of William Tuke (1732–1822): Founder of the modern mental asylum. (August 2016) - Kibria, Ayisha A; Metcalfe, Neil H
William Tuke was a 19th-century reformist and philanthropist notable for his work in mental health. He was known for his strict self-discipline and judicious manner. He was also a firm believer in the Quaker faith and actively supported the group and employed many of their principles in his work, especially in his chef d'oeuvre, The Retreat, established in 1792, a mental asylum in York. Possibly catalysed by the very public mismanagement of King George III's 'madness', he pioneered the use of moral treatment, a new humane method of treating mental illness. This focussed on allowing patients to live in a community, partake in daily activities and not be subjected to the brutality of the commonplace asylum, all of which were very rare in the treatment of lunatics at that time. Described as 'The Period of Humane Reform', his work coincided with the emergence of similar approaches in France, most famously by Philippe Pinel (1745–1826) and his pupil Jean Esquirol (1772–1840) in Paris. Tuke eventually went on to aid in the reform of the law with regards to asylums.